Evaluasi Peggunaan Aplikasi Peduli Lindungi Pada Kalangan Masyarakat Umum Menggunakan Metode Pieces - Ramadani, Indha Suci; Utama Jaya, Joy Nashar (Politeknik Negeri Batam, 2022)
COVID-19 Pandemic makes all Government in the world making somekind of some safety measures into increasing the health safety of it citizen. Efforts have been made to reduce the spread. Indonesian government came up with the